Biometry, size structure and reproductive cycle of the sanded sea cucumbers Holothuria poli (Echinodermata, Holothuriidae) from the west Algerian coast. Issue 1 (2nd January 2022) - Mezali, Karim; Lebouazda, Zineb; Slimane-Tamacha, Farah; Lila Soualili, Dina
ABSTRACT: The aim of this work is to study the biometric and reproductive characteristics of a population of Holothuria poli from the west Algerian coast. The study was carried out on 256 individuals (33.25 ± 12.38 g wet weight and 196.44 ± 37.81 mm relaxed length) collected from Oran Bay between October 2016 and September 2017. All individuals showed negative allometric growth (b = 1.586) and the population had a sex ratio of 1: 1 (male: female). Sexual maturity occurred at a relaxed length of 137 mm and at gutted body weight of 18 g. Macroscopic examination of the gonadal tubules revealed four sexual maturity stages (growth, maturity, spawning and post-spawning) and a reproductive pattern characterized by a single summer spawning period and autumnal sexual rest. The obtained data may constitute a database for the management of natural stocks of this sea cucumber species in Algerian waters.